Evaluation of Phytochemical, Nutritional and Antioxidant Activity of Indigenously Grown Jackfruit (Artocarpus heterophyllus Lam) (Journal of Scientific Research, 2017)
The aim of present investigation was to explore dietary and health benefits of Artocarpus heterophyllus Lam (jackfruit). The nutritional profile of dried ripened jackfruit showed that it is a rich source of carbohydrates (13.08± 0.31%) as well as considerable amount of crude fiber (6.32±0.72 %), crude fat (5.63±0.18 %) and protein (1.48±0.11%) were found. The moisture value and ash content of ripened jackfruit pulp was 71.60±0.75% and 1.89±0.19%, respectively. Among the extracts of ripened jackfruit, in five different solvent systems, methanolic extract exhibited the highest total phenolic (239.87± 0.2 mg GAE/100g dry wt) and flavonoid content (109.94±2.16 mg QE /100g dry wt). Maximum ascorbic acid value (22.47±1.95 mg/100g of dry fruit) was observed in acetone extract of ripened jackfruit pulp. The antioxidant activity of extracts was assessed through DPPH radical scavenging assay. The acetone extract showed higher radical scavenging activity (89.31±0.78%) than remaining extracts. Results of present study enlighten that A. heterophyllus comprising significant nutritional value and high antioxidant potential may be utilized as functional food with towering therapeutic benefits.